An Empirical Analysis of Accounting Students’ Career Plans in Kazakhstan - Чобан, У.; Жубанова, Г. (Journal of Economic Research & Business Administration, 2018)
This study determines the factors influencing accounting students’ choices to pursue their career as a chartered accountant or not. A survey method is used to collect the data. 200 students from 5 different universities from Almaty region participated in this study. Exploratory Factor Analysis (EFA) findings reveal 5 different factors such as; (i) power, (ii) fringe benefits, (iii) soft skills, (iv) personal development as well as (v) physical and emotional safety. Further, it was found that accounting students in Kazakhstan who intend to choose a career in accounting give a much higher priority to their soft skills and financial factors in the form of fringe benefits than those who have chosen other career. The results of this study might have some practical implications as they might open new perspectives for restructuring accounting curriculum. Other implications of this study may help students in the accounting field to understand their abilities and skills, as well as help them better navigate in their future career. Theoretical implications and limitations are discussed.